A Computational Study on a Strategy for Isolating a Stable Cyclopentadienyl Cation. Issue 43 (10th September 2014) - Iversen, Kalon J.; Wilson, David J. D.; Dutton, Jason L.
Abstract: A computational study has been carried out to examine the feasibility of generating a simple monocyclic cyclopentadienyl cation that may be sufficiently stable to isolate and handle at ambient temperatures. Using judicious placement of electron‐withdrawing groups (CF3 ) about the ring we have identified a derivative that may approach the stability of isolobal (and isolatable) borole rings, as evaluated by HOMO–LUMO and singlet–triplet gaps. These Cp + derivatives may therefore be an attractive target for synthetic isolation. Abstract : Computational alchemy : A theoretical evaluation of a variety of simple, monocyclic cyclopentadienyl cations has revealed a potential candidate for the isolation of the first Cp + cation at ambient conditions. The presence of strong electron‐withdrawing groups at the 2 and 5 position of the ring is key to providing a sufficiently large HOMO–LUMO gap for a singlet ground state.